The Effect of Brand Experience on Brand Loyalty Through Brand Trust: A Study on Telemedicine User in Indonesia - Irma Nilasari; Farida Nursjanti; Lia Amaliawiati (Technium Business and Management, 2024)
Telemedicine services in Indonesia show significant potential. This study aims to explore how factors like convenience, affordability, and user satisfaction influence loyalty to telemedicine services. Specifically, it investigates the role of brand trust, encompassing reliability and security, in mediating the relationship between user experience and loyalty. This research focuses on Alodokter, a leading telemedicine service provider in Indonesia. To investigate the relationship between brand experience and brand loyalty, a quantitative study was conducted using a questionnaire survey. The survey was administered to 157 active Alodokter users. The findings revealed that brand experience positively impacts brand loyalty, both directly and indirectly through brand trust reliability. However, brand trust intentionality was not found to mediate this relationship. To further enhance brand loyalty, Alodokter should prioritize improving user experience and addressing technical aspects of brand trust.